Study on Two-phase Flow Mechanisms in Nanopore Considering Microcosmic Deformation and Dynamic Capillary Force. (8th February 2022) - Dou, Xiangji; Lin, Cong; Hong, Sujin; Zhu, Pengfei; Wang, An; Qi, Guodong
Abstract : Coring experiments show that nanopores are extensively distributed in shale oil reservoirs and tend to be deformed when a significant pressure variation exists, and thus the dynamic capillary force phenomenon and flow mechanisms in nanopores can be significantly changed. To characterize the two-phase flow mechanisms in nanopores influenced by the synergistic effect of microcosmic pore deformation and dynamic capillary force, models based on Gassmann's theory are established to describe the variations of pore radius and roughness in a dynamic pressure field. And then, innovative methods to quantify the dynamic capillary force phenomenon under comprehensive influence of pore size, roughness, and pressure are developed. Meanwhile, mathematical models, considering the effect of the pore deformation and dynamic capillary force, are furtherly derived to characterize the water-oil two-phase flow behavior for relatively large nanopores in shale oil reservoir, which can be used to investigate the influence of the vital parameters. The results indicate that the dynamic capillary force phenomenon turns out to be more significant when variations of pore structure and pressure are considered simultaneously. Moreover, the pore deformation and dynamic capillary force caused by pressure change can exert remarkable synergistic influence on the transport capacity for typical flow modes. Bulk modulus is one of the key factors to determine the degree of influence. An optimal pressure can be obtained to coordinate the competitive effect of seepage channel and capillary force for water-drive-oil mode with limited driving force. Based on that, emphasis should be placed on pressure control during the shale oil development process. This work theoretically underpins the quantitative characterization and the analysis of two-phase flow in shale reservoirs at the nanopore scale.